JURNALISME SANTRI MELAWAN HOAKS - Agus Fathuddin Yusuf (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
This article aims to increase awareness of the importance of journalism activities built by pesantren as one of the preaching efforts in the community through santri journalism (santri journalism), increase santri capacity to develop local religious communication and improve santri skills in making journalistic products in the form of news, features, opinions , and articles using social media-based information technology. This is important as an effort to increase the capacity of students as well as efforts to counter narrative lies (hoaks) through the development of citizen journalism in presenting information in the form of journalistic products including news, features, opinions, and articles. Through this, there was an increase in students' knowledge about various journalistic products, variants of information, social media as a form of media convergence, and an increase in the capacity of students as citizen journalists who were critical, caring and responsive to various types of events that occurred around them which were the basic things needed in journalistic work. Keywords: journalism, santri, hoaks